Burden trends and future predictions for hypertensive heart disease attributable to non-optimal temperatures in the older adults amidst climate change, 1990–2021 - Xu, Can; Nie, Xinyu; Xu, Rui; Han, Ge; Wang, Dongjin (Frontiers in Public Health, 2025)
BackgroundHypertensive heart disease (HHD) is a significant form of end-organ damage caused by hypertension, with profound impacts on global health and quality of life. Temperature anomalies driven by climate change, particularly extremes of heat and cold, are increasingly recognized as major contributors to the cardiovascular disease burden, notably impacting HHD. However, the specific spatiotemporal trends and gender-based differences in the burden of non-optimal temperatures on older adults HHD patients remain insufficiently explored. This study aims to evaluate the regional, gender-specific trends in the burden of HHD attributed to non-optimal temperatures among the older adults from 1990 to 2021, and to project future trends in HHD burden under climate-induced temperature anomalies from 2022 to 2050.MethodsData were sourced from the Global Burden of Disease Study (GBD 2021), which provides estimates of mortality and disability-adjusted life years (DALYs) at global, regional, and national levels. Age-standardized rates (ASR) and estimated annual percentage changes (EAPC) were analyzed. Future burden projections were modeled using age-period-cohort (APC) and Bayesian APC models to assess temperature impact by gender and age differences. Data analysis was conducted using R and STATA, examining the variations in temperature effects by gender and age.ResultsBetween 1990 and 2021, cold-related HHD burden among the older adults significantly exceeded that of heat-related burden. However, heat-related HHD burden demonstrated a marked upward trend, projected to continue rising over the next two decades, particularly in low-income and tropical regions. Gender-specific analysis revealed that cold-related HHD burden was more pronounced in women, while heat-related burden was notably higher in men. Additionally, male heat-related HHD mortality rates have shown a substantial increase over the past 30 years, whereas female rates have exhibited a comparatively modest decline.ConclusionAlthough cold remains the dominant non-optimal temperature factor, rising global temperatures suggest an increasing burden of heat-related HHD among the older adults. Efforts should prioritize strengthening resilience in vulnerable regions and populations, with targeted interventions to mitigate future health risks associated with temperature extremes.